STUDENTS’ LEARNING STYLES IN LEARNING ENGLISH SPEAKING OF X GRADE AT SMA NEGERI 1 SIMPANG EMPAT - Novita Sari Lubis; Indra Hartoyo (Universitas Negeri Medan, 2017)
The title of this thesis is Students Learning Style in Learning Speaking of Ten Students at SMA Negeri 1 Simpang Empat. The purpose of conducting this research was to find out whether the most dominant type of students learning style in learning speaking and to find out what is the learning style realized in English Speaking of ten students at SMA Negeri 1 Simpang Empat in academic year 2016/2017. There were 10 students as the subject of this research. In this case, the researcher collected the data by using learning style questionnaire and observation. The result showed that auditory learning style is the most dominant learning style at the tenth grade students at SMA Negeri 1 Simpang Empat, the percentage was 60%, it means 6 from 10 students prefer to hear than read and move. The second was kinaesthetic learning style, the score, 20%, means that only 2 students prefer to move. Then, visual learning style has same dominant with kinesthetic, the score, 20% , means that 2 from 10 students prefer to read. For the fastest student’s in reading comprehension came from auditory students or auditory learners. They get score 50%, followed visual 20%, and visual 10%.